Government and Institutional Support for Pesantren Entrepreneurship: An Economic Law Analysis - Anas Alhifni (TRUNOJOYO LAW REVIEW, 2026)
This study examines the legal and regulatory frameworks shaping entrepreneurship in Indonesian pesantren, focusing on the application of economic law within Islamic boarding schools. Specifically, it investigates business licensing and Islamic finance law, with an emphasis on how these regulations influence the entrepreneurial practices within pesantren. Using a mixed-methods approach, the study combines quantitative data from surveys of 150 stakeholders and qualitative insights from interviews with 27 informants at Pesantren Sunan Drajat in Lamongan, East Java. The research identifies a strong alignment between pesantren entrepreneurship and national economic development policies, particularly in micro, small, and medium enterprises (MSMEs). However, it also reveals significant regulatory gaps in business formalization, intellectual property protection, and access to Islamic financial resources, thereby hindering entrepreneurial growth. This study contributes to the fields of institutional economics and legal pluralism, offering a detailed analysis of the pesantren system as a hybrid institution combining religious education with economic activity. The study argues for a more integrated economic legal framework that is responsive to the unique socio-religious needs of pesantren, recommending enhanced legal facilitation, expanded financial access, and more effective institutional support mechanisms.